Perceived teacher affective support in relation to emotional and motivational variables in elementary school science classrooms in Turkey. Issue 1 (2nd January 2017) - Sakiz, Gonul
Abstract: Background: In recent research, affective learning environments and affective support have been receiving increasing attention for their roles in stimulating students' learning outcomes. Despite its raising importance, little is known about affective support in educational contexts in developing countries. Moreover, international student assessment programmes (e.g. PISA and TIMSS) reveal poor science proficiency of students in most of those countries, which provokes the question of how to make positive changes in students' perspectives and attitudes in science. Purpose: In the current study, the purpose was to investigate the relations among perceived teacher affective support (PTAS), academic emotions (academic enjoyment, academic anxiety, and academic hopelessness), academic self-efficacy and behavioural engagement in elementary school science classrooms in Turkey. Sample: A total of 633 fourth- and fifth-grade students in eight elementary schools in Istanbul, Turkey were participated in the study. Design and methods: A self-report questionnaire was administered to participating students. The data were analysed using structural equation modelling. Results: Findings showed that PTAS was both directly and indirectly related to the given variables. PTAS was found to be significantly positively associated with students' academic enjoyment, academic self-efficacy and behavioural engagement and significantly negatively related to their academic anxiety and academic hopelessness in science classrooms. An important finding is that the total effect of PTAS on behavioural engagement, a factor strongly associated with academic success in all disciplines, was as strong as the effect of students' perceived academic self-efficacy beliefs in science. Conclusions: Findings suggest that PTAS may help promoting positive emotions and motivation among students in science classrooms, eventually leading to more desirable attitudes and achievement outcomes in science. Teacher affective support deserves greater recognition from researchers, educational policy-makers, administrators and teachers to build better learning conditions for all students.